A RECOMMENDATION MODEL FOR SELECTING INTERNSHIP PLACEMENTS FOR DIGITAL BUSINESS STUDENTS AT TELKOM UNIVERSITY PURWOKERTO THROUGH AN ANP APPROACH - Muhammad Kadek Fajri Mayliawan; Muhammad Ikhsan; Muhammad Ilham; Muhammad Eka Purbaya (Fakultas Ilmu Komputer Universitas Duta Bangsa Surakarta, 2026)
In the face of digital industry transformation and global competition, students are required to be well-prepared before entering the workforce. Internships are a strategic solution to bridge the gap between graduate competencies and industry needs, but the variety of alternative internship places demands a systematic selection process. This research aims to develop a recommendation model for selecting internship places based on the Analytical Network Process (ANP) method for students of the Telkom University Purwokerto Digital Business Study Program. Data was obtained through a paired comparison questionnaire to experts, as well as historical data from previous internship partners. The results showed that the Career Opportunities and Networking criteria had the highest global weight (0.35942), with the main sub-criteria of company name and reputation (0.056016) and the opportunity to be recruited after internship (0.045611). Startup internship alternatives received the highest weight, followed by Large-Scale Private Companies and State-Owned Enterprises. The ANP model built is able to capture the interrelationships between elements in the decision-making process adaptively and systematically. These findings contribute to the design of internship programs that are more relevant to student needs and encourage educational institutions to establish strategic partnerships with industries that support student career development.